Topologically-mediated energy release by relativistic antiferromagnetic solitons - R. M. Otxoa; R. Rama-Eiroa; P. E. Roy; G. Tatara; O. Chubykalo-Fesenko; U. Atxitia (Physical Review Research, 2021)
Magnetic solitons offer functionalities as information carriers in multiple spintronic and magnonic applications. However, their potential for nanoscale energy transport has not been revealed. Here we demonstrate that antiferromagnetic solitons, e.g., domain walls, can uptake, transport, and release energy. The key for this functionality resides in their relativistic kinematics; their self-energy increases with velocity due to Lorentz contraction of the soliton and their dynamics can be accelerated up to the effective speed of light of the magnetic medium. Furthermore, their classification in robust topological classes allows us to selectively release this energy back into the medium by colliding solitons with opposite topology. Our work uncovers important energy-related aspects of the physics of antiferromagnetic solitons and opens up the attractive possibility for spin-based nanoscale and ultrafast energy transport devices.